2018
DOI: 10.2147/ott.s180785
|View full text |Cite|
|
Sign up to set email alerts
|

Polydatin exerts anti-tumor effects against renal cell carcinoma cells via induction of caspase-dependent apoptosis and inhibition of the PI3K/Akt pathway

Abstract: PurposePolydatin, a stilbenoid glucoside of a resveratrol derivative, has many biological functions, including antitumor effects. However, the antitumor effects of polydatin in renal cell carcinoma (RCC) have not been investigated.Materials and methodsIn the current study, MTT assays, transwell invasion assays and wound healing assays were performed to examine cell proliferation, invasion and migration. An apoptosis nucleosome ELISA was used to measure apoptosis. Caspase activity assays were applied to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In fact, biomaterials have an important dual purpose: to release the antitumor drugs in the bone at the place of surgical intervention and to mimic the bone microenvironment by inducing tissue regeneration [20]. Polydatin, a natural glycosylate precursor of resveratrol, has been reported to have an antitumor effect by inhibiting the PI3K/Akt and PDGF/Akt pathway [29][30][31][32]. It was reported that polydatin inhibited the proliferation and promoted the apoptosis of OS cells through upregulation of the Bax/Bcl-2 ratio and attenuation of β-catenin signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, biomaterials have an important dual purpose: to release the antitumor drugs in the bone at the place of surgical intervention and to mimic the bone microenvironment by inducing tissue regeneration [20]. Polydatin, a natural glycosylate precursor of resveratrol, has been reported to have an antitumor effect by inhibiting the PI3K/Akt and PDGF/Akt pathway [29][30][31][32]. It was reported that polydatin inhibited the proliferation and promoted the apoptosis of OS cells through upregulation of the Bax/Bcl-2 ratio and attenuation of β-catenin signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 2-Cl-MGV-1 achieved a significant protective effect on the same biological processes (Figures 1, 4 One of the main intracellular functions of TSPO is its regulatory role in apoptotic cell death [12,13]. Caspase-dependent apoptosis was previously demonstrated to be sensitive to TSPO ligands [24,25,43,44]. In this study, caspase-dependent apoptosis was expressed by the significant elevation in cell death levels along with the apoptotic markers caspases 3, 8 and 9 following 60 min of CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin has showed anticancer effects against various tumours in laboratory, including breast cancer, liver cancer and renal cancer (55)(56)(57) . Efforts in the field of bone cancer are mainly devoted to osteosarcoma, and a broad spectrum of cell responses have been found to be involved in the anti-osteosarcoma process of polydatin (Fig.…”
Section: Anticancer Effects Of Polydatin On Bonesmentioning
confidence: 99%